Respuesta :
Answer:
Listed below
Step-by-step explanation:
This is a function composition excercise. The idea is to sustitute the value of G(x) in the X's value of the other function.
a) [tex]f(x)=x+9[/tex] and [tex]g(x)=\frac{4}{x^{2} }[/tex]
So we replace g(x) on the X of the f(x) function and we get:
[tex]f(g(x))=\frac{4}{x^{2} } +9[/tex]
b) We do the same on this excercise:
[tex]f(x)=x[/tex] and [tex]g(x)[tex]f(g(x))=\frac{4}{x+9}[/tex][/tex]
We replace and we get:
c) And the same on this one:
[tex]f(x)=\frac{1}{x}[/tex] and [tex]g(x)=\frac{4}{x+9}[/tex]
We replace and we get:
[tex]f(g(x))=\frac{1}{\frac{4}{x+9} } = 1: \frac{4}{x+9} =1.\frac{x+9}{4} =\frac{x+9}{4}[/tex]
d) Exactly the same on this excercise:
[tex]f(x)=\frac{4}{x^{2} }[/tex] and [tex]g(x)=9[/tex]
We replace:
[tex]f(g(x))=\frac{4}{9^{2} } = \frac{4}{81}[/tex]